Social networks and factor markets: Panel data evidence from Ethiopia - Abay, Kibrom A.; Kahsay, Goytom A.; Berhane, Guush (International Food Policy Research Institute, 2014)
We investigate the role of an indigenous social network in Ethiopia, the iddir, in facilitating factor market transactions among smallholder farmers. Using detailed longitudinal household survey data and employing a difference-in-differences approach, we find that iddir membership improves households’ access to factor markets.